2017
DOI: 10.1111/mec.14088
|View full text |Cite
|
Sign up to set email alerts
|

The within‐host dynamics of infection in trans‐generationally primed flour beetles

Abstract: Many taxa exhibit plastic immune responses initiated after primary microbial exposure that provide increased protection against disease-induced mortality and the fitness costs of infection. In several arthropod species, this protection can even be passed from parents to offspring through a phenomenon called trans-generational immune priming. Here, we first demonstrate that trans-generational priming is a repeatable phenomenon in flour beetles (Tribolium castaneum) primed and infected with Bacillus thuringiensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
105
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(111 citation statements)
references
References 61 publications
5
105
1
Order By: Relevance
“…Thus, priming perhaps rescues post‐infection by reducing the pathogen load. Prior studies also show that priming alters bacterial load, though the timing (Tate, Andolfatto, Demuth, & Graham, ) and direction of the impact varies (compare Pham, Dionne, Shirasu‐hiza, & Schneider, ; Kutzer, Kurtz, & Armitage, ). Together, these results indicate that pathogen‐mediated reduction in life span may impose strong selection for a priming response in natural populations, as predicted by theoretical models (Best et al, ) and observed in laboratory‐evolved populations (Khan et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, priming perhaps rescues post‐infection by reducing the pathogen load. Prior studies also show that priming alters bacterial load, though the timing (Tate, Andolfatto, Demuth, & Graham, ) and direction of the impact varies (compare Pham, Dionne, Shirasu‐hiza, & Schneider, ; Kutzer, Kurtz, & Armitage, ). Together, these results indicate that pathogen‐mediated reduction in life span may impose strong selection for a priming response in natural populations, as predicted by theoretical models (Best et al, ) and observed in laboratory‐evolved populations (Khan et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Within each experiment, we performed qPCR for each transcript template using PowerUp Sybr Green Master Mix (Life Technologies) on the QuantStudio 6 machine (Applied Biosystems) by running all individuals on the same 384 well plate in duplicate, where possible, using default settings unless indicated in Table . We confirmed equivalent Ct thresholds and ran a subset of individuals on both plates to minimize plate effects, as in (Tate et al, ).…”
Section: Methodsmentioning
confidence: 82%
“…Bacillus thuringiensis is a spore‐producing entomopathogen that relies on host killing for transmission (Raymond, Johnston, Nielsen‐LeRoux, Lereclus, & Crickmore, ). Whether it naturally enters the host through the gut or is septically injected, it grows rapidly in the haemolymph of infected beetles and kills them within 12 hr (Tate et al, ). To infect beetles with Bt (ATCC 55177, a berliner strain that contains a cry protein gene active against Coleoptera), we prepared a culture from a glycerol stock kept at −80°C and grown overnight in 10 ml of Nutrient Broth #3 (Sigma Aldrich).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations